Muslim Intellectuals’ Insights and Their Contributions to the Development of Alternative Social Science in the Malay-Indonesian Context - Hasnan Bachtiar; Zakiyuddin Baidhawy (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
This article aims to examine the interaction between social science and tradition in Malay-Indonesian scholarship, with a particular focus on the perspectives of Muslim intellectuals. This interaction is represented by two approaches: autonomous social science and prophetic social science. The article argues that both approaches have their distinct inclinations in perceiving and formulating theoretical foundations. These inclinations are shaped by their unique qualities, alternative values, intellectual stances, and thinking styles. Moreover, during the process of development, they are influenced by various factors that give them their distinct characteristics, such as autonomy, a problem-based approach, and a strong commitment to rethinking society and driving change and transformation. The social concept of Islam Nusantara represents this development. It is a collection of arguments and practices of Islam adopted by Muslims in Nusantara, which have shaped patterns of social relations and cohesiveness through communicative actions throughout a specific historical epoch in the region. The article also highlights two essential factors that significantly shape these approaches: the dominant schools of thought in social science and the peculiar Malay-Indonesian traditions. While Western social sciences have played a central role in understanding certain concepts, Malay-Indonesian traditions have contributed significantly to shaping the paradigm of local scholars.